Determinant of the Prevalence of Undernourishment (POU) in Districts/Cities of Papua Province from 2021–2024 - Wennar Tamara; Inda Fresti Puspitasari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The study aims to analyze factors related Prevalence of Undernourishment (PoU) in 29 districts and city of Papua Province from year 2021-2024. The proportion of the population that does not consume enough energy is PoU. Panel data regression model using the Fixed Effect Model (FEM) was employed in the analysis. Variables such as economic growth, poverty, population density, average length of schooling and life expectancy have been considered. The estimation results show that the PoU is negatively and significantly influenced by economic growth, while number of poor people and life expectancy have a positive and significant influence. These findings confirm that increasing economic growth and reducing poverty are important strategies for reducing food insecurity in Papua. Thus, the implementation of policies focused on inclusive economic growth and poverty alleviation is expected to support the achievement of Sustainable Development Goal (SDG) 2, “Zero Hunger,” while improving the welfare of the community.